Livestock and water management: Key for changing systems and livelihoods in Africa - Amede, Tilahun; Descheemaeker, Katrien K. (2008)
Livestock is a key livelihood strategy and source of food and income for poor livestock keepers. However, inappropriate livestock management along with poor water management practices often contributes to widespread and severe depletion, degradation and contamination of water and land resources. The negative effect of livestock on water depletion is becoming a global concern, particularly associated with climate change and water scarcity. Livestock-Water Productivity (LWP) refers to a set of ideas that could contribute towards reducing the amount of water needed per unit of output generated. It is a strategy to reverse the inefficient livestock and water management practices, which often contributes to widespread and severe depletion, degradation and contamination of water and land resources. There is compelling need for better understanding of the nature of livestock-water interactions. Yet, great opportunities remain to further reduce domestic animals use of water. In tegrating livestock and water planning, Development and management has the potential to help reduce poverty, increase food production and reduce pressure on the environment including scarce water resources. Major strategies that could help achieve this are choosing water efficient feed sources, improved in situ and ex situ water management practices associated with crop-livestock management, improved animal management for efficient resource use efficiency and improved veterinary services. Achieving integrated livestock-water Development will also require new ways of thinking about managing water by water and animal sciences professionals. But what does it take to get these ideas adopted by livestock keepers in crop-livestock systems? This paper explores the nature of innovation adoption, and argues that, in the under-regulated crop-livestock systems of eastern Africa, it makes sense to focus in on social institutions as an entry point for adoption.